-2(k-14)+4=-6

Simple and best practice solution for -2(k-14)+4=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(k-14)+4=-6 equation:


Simplifying
-2(k + -14) + 4 = -6

Reorder the terms:
-2(-14 + k) + 4 = -6
(-14 * -2 + k * -2) + 4 = -6
(28 + -2k) + 4 = -6

Reorder the terms:
28 + 4 + -2k = -6

Combine like terms: 28 + 4 = 32
32 + -2k = -6

Solving
32 + -2k = -6

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-32' to each side of the equation.
32 + -32 + -2k = -6 + -32

Combine like terms: 32 + -32 = 0
0 + -2k = -6 + -32
-2k = -6 + -32

Combine like terms: -6 + -32 = -38
-2k = -38

Divide each side by '-2'.
k = 19

Simplifying
k = 19

See similar equations:

| 2p+5q=15 | | 2m+12=m+15 | | 12x+2=-8+22 | | 7.3d+14.26=6.4d+1.93 | | X^2+22x+110=0 | | 2x^2y^4+4x^3y^3= | | 7+5x=2x+-2 | | 2(x-4)-3=6x-4(4+x) | | -16k=-18-17k | | 2(x-4)-3=6x-4(4+6) | | 6x-1+x=90 | | 3/5-1/5= | | 17b+15+4b^2= | | 17f+5=16f-10 | | 46.12-29d-0.8=d | | (x/3)-4=(x/5)-2 | | n^2+n-360=0 | | 5(m-1)+16(2m+3)=3(2m-7)-m | | 27+yi=11-x+8i | | 6r+2-14r=-7r-17 | | 2x^(3/5)=27 | | 10y^3-4y^2= | | 25x^6-9a^6= | | 3j+10=j | | -8u+9=-5u | | 4+14X^2-7x= | | (-7z-8)-(z+2)=-15z-87 | | -8+8g=2g+10g+4 | | -2-9s=-8-10s | | log(5x-1)+log(x+5)=1 | | 3x+4(x-3)=72 | | 14x^2+14x^2-7x= |

Equations solver categories